2007
DOI: 10.1126/science.1143304
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén Waves in the Solar Corona

Abstract: Alfvén waves, transverse incompressible magnetic oscillations, have been proposed as a possible mechanism to heat the Sun's corona to millions of degrees by transporting convective energy from the photosphere into the diffuse corona. We report the detection of Alfvén waves in intensity, line-of-sight velocity, and linear polarization images of the solar corona taken using the FeXIII 1074.7-nanometer coronal emission line with the Coronal Multi-Channel Polarimeter (CoMP) instrument at the National Solar Observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
802
3
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 782 publications
(843 citation statements)
references
References 25 publications
36
802
3
2
Order By: Relevance
“…This effectively imposes a lower limit for the period of kink waves observable in the corona. This is consistent with the observed periods of coronal waves (e.g., Tomczyk et al 2007;Tomczyk & McIntosh 2009;McIntosh et al 2011). …”
Section: Chromospheric Kink Wavessupporting
confidence: 77%
See 2 more Smart Citations
“…This effectively imposes a lower limit for the period of kink waves observable in the corona. This is consistent with the observed periods of coronal waves (e.g., Tomczyk et al 2007;Tomczyk & McIntosh 2009;McIntosh et al 2011). …”
Section: Chromospheric Kink Wavessupporting
confidence: 77%
“…Therefore, it was predicted that high-frequency kink waves become damped in length scales shorter than low-frequency waves. Verth et al (2010) showed that this result is consistent with the CoMP observations of damped coronal waves (Tomczyk et al 2007;Tomczyk & McIntosh 2009). Subsequent investigations have extended the original work by TGV by incorporating effects not considered in their paper.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Ion cyclotron heating and the turbulent cascade models exploit the notion that low frequency shear Alfven waves excited in the chromosphere will survive into the lower corona. Upward propagating Alfven modes have been observed in the chromosphere (de Pontieu et al 2007), in the lower corona by Hinode (Ofman and Wang 2007;Okamoto et al 2007) and by ground-based detectors (Tomczyk et al 2007). The ion cyclotron heating mechanism proceeds by resonant wave particle interactions with Alfven waves, leading to heating of the solar corona (Isenberg 2001b(Isenberg , 2004.…”
Section: Heating the Corona And Solar Windmentioning
confidence: 99%
“…Special program of TRACE observation made possible by De Groof et al (2004) to detect and investigate propagating disturbances in loop. Tomczyk et al (2007) reported about very interesting observation of oscillation of velocities field in quiet system of loop using Coronal Multichannel Polarimeter.…”
Section: Introductionmentioning
confidence: 99%